2020
DOI: 10.5194/wes-2020-5-ac2
|View full text |Cite
|
Sign up to set email alerts
|

Response to RC2

Abstract: Interactive comment on "Multipoint Reconstruction of Wind Speeds" by Christian Behnken et al. Christian Behnken et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Manipulation of the regulatory elements involved in the global activation of secondary metabolism in R. cellulolyticum sustained the production of closthioamide and allowed isolation of seven congeners which showed varied levels of bioactivity. 40 Evaluation of the antibacterial activity of the congeners demonstrated the importance of all six thioamide moieties, terminal aromatic residues, the modular arrangement of the β-thioalanyl units, and the distinct length of spacer units for antibacterial activity. 40,41 Moreover, it was also found that closthioamide is a selective Cu(I) chelator akin to methanobactin and forms a compact symmetrical dinuclear copper complex.…”
Section: Thioamides In Nature: Biosynthesis Structure and Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…Manipulation of the regulatory elements involved in the global activation of secondary metabolism in R. cellulolyticum sustained the production of closthioamide and allowed isolation of seven congeners which showed varied levels of bioactivity. 40 Evaluation of the antibacterial activity of the congeners demonstrated the importance of all six thioamide moieties, terminal aromatic residues, the modular arrangement of the β-thioalanyl units, and the distinct length of spacer units for antibacterial activity. 40,41 Moreover, it was also found that closthioamide is a selective Cu(I) chelator akin to methanobactin and forms a compact symmetrical dinuclear copper complex.…”
Section: Thioamides In Nature: Biosynthesis Structure and Functionmentioning
confidence: 99%
“…40 Evaluation of the antibacterial activity of the congeners demonstrated the importance of all six thioamide moieties, terminal aromatic residues, the modular arrangement of the β-thioalanyl units, and the distinct length of spacer units for antibacterial activity. 40,41 Moreover, it was also found that closthioamide is a selective Cu(I) chelator akin to methanobactin and forms a compact symmetrical dinuclear copper complex. 13,42 Through synthesis and application of deuterium-and fluorine-labeled probes (see below), initial insights into closthioamide biosynthesis were obtained, which predicted the involvement of an unusual non-ribosomal peptide synthetase (NRPS).…”
Section: Thioamides In Nature: Biosynthesis Structure and Functionmentioning
confidence: 99%
See 2 more Smart Citations